The immunological response of wistar rats with oral candidiasis - Mustafa Al-Ahmad, Basma Ezzat (2017)
Candidiasis caused by Candida albicans, which is the most virulent species that can colonize in the oral mucosa. A major virulence factor of Candida albicans is its ability to adapt to different environments, the resulting is formation of surface-attached microbial communities known as biofilms. The treatment of mucosal infections caused by candida and the elucidation of the disease is challenging. Therefore, the study of experimentally induced oral candidiasis in rats is useful to clarify the etiopathology of this condition, improve diagnosis, and search for new therapeutic designs in which it is similar to human. When growing on a medical device or mucosal surface, Candida albicance reside as communities embedded in a protective matrix, usually they resist the host defenses, which include depositing and incorporation of several proteins into the biofilm matrix. Leukocytes are less effective against Candida albicans within a biofilm. This study is describing the host’s response to Candida biofilms using different materials of the appliances used in animal model which mimicked clinical denture stomatitis. Palatal candidiasis can be seen after one week of fitting the dentures on the rat palate, while during the second week alternating epithelial hyperplasia and atrophy occurs, Intra-epithelial polymorphonuclear leukocyte infiltration and chronic inflammatory cell infiltration in the underlying connective tissue was observed in addition to the presence of some protective antibodies . The transmission of candida from blastospore to mycelium occurs after one week and mycelium is predominated at the third week, however hyperorthokeratinization at the fourth week was observed. This constitutes a good evidence for anti candidal protection during oral candidiasis. This will have the potential for including such studies as a powerful tool in understanding the pathogenesis, host interactions, and management of oral mucosal candidal infections.